TRAJET ET RELATIONS DE LA BRANCHE EXTERNE DU NERF ACCESSOIRE AU NIVEAU DE LA PREMIERE PARTIE DE LA VEINE JUGULAIRE INTERNE - Piffer, C. R.; Garcia, P. J.; Soares, J. C. (My University, 1980)
This report is based upon microdissections of 32 right and left hemi-heads. It was observed in 26 pieces of both sides that the external branch of the accessory nerve turns round the medial surface and next the posterior surface of the first portion of the internal jugular vein. In 6 pieces obtained from both sides it was observed that the nerve turns round the anterior surface and next the lateral surface of the internal jugular vein. In the superior portion of the neck, the accessary nerve is also in the interior of the carotid sheath and is involved by a subdivision of this sheath. At this level, the nerve peforates the carotid sheath and runs down obliquely, outside and behind the deep surface of the sternocleidomastoid and the trapezius muscles.
Course of the external branch of the accessory nerve and its relations with the first portion of the internal jugular vein